Characterization of the Physiological Response following In Vivo Administration of Astragalus membranaceus. (12th April 2016) - Denzler, Karen; Moore, Jessica; Harrington, Heather; Morrill, Kira; Huynh, Trung; Jacobs, Bertram; Waters, Robert; Langland, Jeffrey
Abstract : The botanical, Astragalus membranaceus, is a therapeutic in traditional Chinese medicine. Limited literature exists on the overall in vivo effects of A. membranaceus on the human body. This study evaluates the physiological responses to A. membranaceus by measuring leukocyte, platelet, and cytokine responses as well as body temperature and blood pressure in healthy individuals after the in vivo administration of A. membranaceus . A dose-dependent increase in monocytes, neutrophils, and lymphocytes was measured 8–12 hours after administration and an increase in the number of circulating platelets was seen as early as 4 hours. A dynamic change in the levels of circulating cytokines was observed, especially in interferon- γ and tumor necrosis factor- α, IL-13, IL-6, and soluble IL-2R. Subjective symptoms reported by participants were similar to those typically experienced in viral type immune responses and included fatigue, malaise, and headache. Systolic and diastolic blood pressure were reduced within 4 hours after administration, while body temperature mildly increased within 8 hours after administration. In general, all responses returned to baseline values by 24 hours. Collectively, these results support the role of A. membranaceus in priming for a potential immune response as well as its effect on blood flow and wound healing.